Diseño de máquina inyectora de termoplásticos para fabricación de suelas, con doble boquilla de salida (2017)
The project began with the detailed description of the current state of plastic injection machines, their nozzles and the characteristics of the material used for manufacturing soles. Then, with the parameterization and conceptualization of the process performed by this type of machines, the conditions to which the elements of the injector are subjected in normal operations were evaluated. With the information collected, design alternatives were established for the injection system, nozzle and double outlet nozzle, design of machine elements and analysis of finite elements to verify the correct operation of the injection system and its structure, which supports : Worm screw, jacket, resistances, hopper with the material to be injected and gearmotor, this throws us a safety factor, where you can know the relative safety measure, with which the structure was designed and that this will not fail While in operation.